Incidence of patent foramen ovale and migraine headache in adults with congenital heart disease with no known cardiac shunts. Issue 4 (14th November 2012) - Volman, Marat; Mojadidi, M. Khalid; Gevorgyan, Rubine; Kaing, Amy; Agrawal, Harsh; Tobis, Jonathan
<x xml:space="preserve">Abstract</x> The purpose of this study was to understand why patients with adult congenital heart disease (CHD) but no obvious shunt have an increased frequency of migraine headaches (MH). CHD patients with no known cardiac shunts (CHD‐NKS), based on their echocardiographic or angiographic procedures, were tested for a right‐to‐left shunt using agitated saline contrast transcranial Doppler (TCD). Medical records of 2, 920 patients from the UCLA Adult CHD Center were screened to participate in a study to evaluate the prevalence of MH in adults with CHD; 182 patients (6.23%) had CHD‐NKS; of these, 60 (30%) underwent a TCD; 23 (38%) tested positive and 37 (62%) tested negative for a right‐to‐left shunt (P = 0.01 compared with controls). The frequency of MH was 43% in CHD‐NKS compared with 11% in controls (P < 0.0001). TCD demonstrated right‐to‐left shunting in approximately 2/3 of patients with pulmonary stenosis, the Marfan syndrome and congenitally corrected transposition of great vessels, 1/4 of patients with bicuspid aortic valve, 1/5 of patients with mitral valve prolapse and all patients with Ebstein's anomaly. Approximately half of these experienced MH. Patients who had MH did not show a higher frequency of right‐to‐left shunt when compared with patients without MH (P = 0.57). In conclusion, CHD patients with conditions usually not associated with a shunt have a higher than expected prevalence of PFO which permits intermittent right‐to‐left shunting undetected by standard non‐contrast TTE and TEE; the increased prevalence of right‐to‐left shunting may partially explain the higher than expected frequency of migraines. © 2012 Wiley Periodicals, Inc.